Characterization, Genomic Organization, Abundance, and Chromosomal Distribution of Ty1-copia Retrotransposons in Erianthus arundinaceus - Huang, Yongji; Luo, Ling; Hu, Xuguang; Yu, Fan; Yang, Yongqing; Deng, Zuhu; Wu, Jiayun; Chen, Rukai; Zhang, Muqing (Frontiers in Plant Science, 2017)
Erianthus arundinaceus is an important wild species of the genus Saccharum with many valuable traits. However, the composition and structure of its genome are largely unknown, which have hindered its utilization in sugarcane breeding and evolutionary research. Retrotransposons constitute an appreciable fraction of plant genomes and may have played a significant role in the evolution and sequence organization of genomes. In the current study, we investigate the phylogenetic diversity and genomic abundance of Ty1-copia retrotransposons for the first time and inspect their chromosomal distribution patterns in E. arundinaceus. In total, 70 Ty1-copia reverse transcriptase (RT) sequences with significant levels of heterogeneity were obtained. The phylogenetic analysis revealed these Ty1-copia retrotransposons were classified into four distinct evolutionary lineages (Tork/TAR, Tork/Angela, Retrofit/Ale, and Sire/Maximus). Dot-blot analysis showed estimated the total copy number of Ty1-copia retrotransposons to be about 4.5 × 103 in the E. arundinaceus genome, indicating they were a significant component. Fluorescence in situ hybridization revealed that Ty1-copia retrotransposons from the four lineages had strikingly similar patterns of chromosomal enrichment, being exclusively enriched in the subterminal heterochromatic regions of most E. arundinaceus chromosomes. This is the first clear evidence of the presence of Ty1-copia retrotransposons in the subterminal heterochromatin of E. arundinaceus. Altogether, these results promote the understanding of the diversification of Ty1-copia retrotransposons and shed light on their chromosomal distribution patterns in E. arundinaceus.